Efficient Internet traffic delivery over wireless networks. - Mukhtar, R.G (IEEE Communications magazine)
The high demand for wireless Internet connectivity has driven the development of highly efficient radio link technologies. However, their performance can be compromised by inadvertent interactions with the higher-layer TCP flow control protocol. Maximizing the performance of wireless links requires that mechanisms operating at every layer of the protocol stack interact efficiently. This article provides a brief tutorial of some of these radio link enhancements. It then outlines how higher-layer flow control protocols should behave, and provides techniques for taming the behavior of TCP, to ensure that the performance of lower-layer enhancements is not compromised.